PEMIKIRAN PENDIDIKAN ISLAM BERBASIS EKOTEOLOGI DALAM MENGHADAPI KRISIS IKLIM GLOBAL - Sultan Sultan (STAI Sangatta Kutai Timur, 2026)
The global climate crisis demands the development of an educational paradigm capable of building ecological awareness. However, environmental education is still dominated by technical and scientific approaches, while Islamic education is more oriented towards the formation of spiritual and social piety. This condition indicates that the ecological dimension has not been systematically integrated into contemporary Islamic educational thought. This study aims to reconstruct Islamic educational thought based on ecotheology as an alternative paradigm in responding to the global climate crisis. This study uses a qualitative approach with library research methods through a critical analysis of Islamic education literature, ecotheology, and contemporary environmental studies. Data are analyzed using thematic and contextual analysis to identify ecological principles relevant to the development of Islamic education. The results show that the concepts of tawhid, khalifah, amanah, mizan, and islah have epistemological and axiological potential to reconstruct the goals, orientation, and practices of Islamic education that are more ecologically responsive. This reconstruction shifts the orientation of Islamic education from the formation of individual piety to ecological piety that places responsibility for the environment as an integral part of devotion to Allah SWT. The research contributes to the development of an ecotheology-based Islamic education paradigm that integrates spiritual, ethical, and ecological dimensions in facing the challenges of the global climate crisis and broadens contemporary discourse on the relationship between religion, education, and environmental sustainability.